Nontypeable Haemophilus influenzae: The Role of N-Acetyl-5-Neuraminic Acid in Biology - Apicella, Michael A. (Frontiers in Cellular and Infection Microbiology, 2012)
NTHi is an exclusive human pathogen, which has evolved a number of unique mechanisms to survive within the human environment. An important part of this is the ability of the organism to take up and incorporate sialic acid into its surface structures. This protects the organism against host adaptive and innate immune factor as well as serving as a mechanism for sustaining itself within biofilms. Recent evidence suggests that this also may be the source of the evolution of human antibodies to non-human sialic acid structures, which can lead to inflammation in the host. In very rare instances, evolution of antibodies to sialylated LOS mimics of human antigens can result in autoimmune disease.